COMPOSITION AND STRUCTURE OF THE EARTH BEETLE (COLEOPTERA, CARABIDAE) FAUNA OF THE ZARAFSHAN MOUNTAIN RANGE - Omonova Sevara Akramjonovna (Modern American Journals, 2025)
This article examines the composition, ecological structure, and geographical distribution of the earth beetle (Coleoptera: Carabidae) fauna in the Zarafshan mountain range. The research was conducted in 2023 using pitfall-trap and hand-picking methods at various altitudes. The results show that 45 species of ground beetles are found in the Zarafshan mountain range, with species such as Carabus, Pterostichus, Nebria, and Calosoma constituting the main group. Changes in altitude affect the number of species and their distribution in ecological zones.It is noted that this territory is important for ensuring biological diversity and ecological balance for the fauna of earth beetles. The research results can serve as a basis for the development of environmental monitoring and environmental protection programs.
Keywords: Zarafshan mountain range, earth beetles, Carabidae, ecological structure, biodiversity, altitudinal distribution.